Gamification in accounting learning: As a key factor to learn playing at a University in Peru - Montoya, David De la Cruz-; Orbegoso, Lorenzo Zavaleta; Vega, Iris López; Rubio, Edith Silva; Ortiz, Paola Julca (Edelweiss Applied Science and Technology, 2025)
The purpose of this study is to establish the influence of educational gamification on accounting learning among accounting students at a Peruvian university. The methodology adopted for this research included accounting students from the Financial Statement Evaluation (28 students) and Business Finance (15 students) courses. Participants were given pre- and post-tests and engaged in educational games such as Cash Flow, financial simulators, and case studies on financial ratio evaluation. A normality test was performed using the Wilcoxon test. The results showed that, according to the statistical tests applied, 93% of students demonstrated significant improvements in learning in the Financial Statement Evaluation course, and 100% reported significant improvements in the Business Finance course. Games such as Cash Flow and Labsag simulators also showed significant improvements in learning in the aforementioned courses. Students exhibited increased motivation, commitment, and understanding of the course material. Therefore, it is concluded that gamification has led to significant improvements in accounting learning among students at a university in Peru.